Labor Market Regulations and Income Inequality: Evidence for a Panel of Countries - César Calderón; Alberto Chong; Rodrigo Valdés (Inter-American Development Bank, Research Department, 2004)
This paper presents evidence on the impact of labor regulations on income inequality using two recently published databases on labor institutions and outcomes (Rama and Artecona, 2002; Botero, Djankov, La Porta, López-de-Silanes and Shleifer, 2003) and different cross-section and panel data analysis techniques for a sample of 121 countries over the 1970-2000 period. When we consider the techniques most likely to be robust, we find that: (i) de jure regulations do not improve income distribution; (ii) relative compliance with existing regulations improves income distribution; (iii) de facto regulations are weakly associated with improving income inequality. This result partly reflects the fact that regulations are endogenous and, more interestingly, different regulations have quite distinct effects. In particular, we find that any redistributive effect of labor regulations may come from trade union membership, public employment and mandated benefits (proxied by maternity leave).
Keywords: 330; Arbeitsmarktpolitik; Einkommensverteilung; Welt